THERMAL ANALYSIS OF FATS USING THE «TERMOSCAN» UNIT - Mayorov A.A.; Usatyuk D.A. (Техника и технология пищевых производств)
This article describes the installation of «Termoscan». This device allows us to study fats of different origin on thermal effects (in the temperature range from minus 9 °C to plus 60 °C) during their heating and cooling. Differential thermograms of heating and cooling of milk fat, pork fat and SOYUZ 71E fat mixture have been obtained. Two sections with extreme points in the heating and cooling processes have been determined. Exact data on the extrema obtained have been tabulated. The tables show the results of studies on temperature and temperature effect obtained from extremum No. 1 and extremum No. 2 (the mean, deviation from the mean and deviation from the mean in percentage). The data obtained are also presented graphically. Comparison of the data of the results in the study of the tested samples has been made. The reliability factor as the ratio of the difference in the temperatures of the two fats to the sum of the deviations in the measurements has been calculated. The results obtained during the series of experiments make it possible to judge the correctness and reliability of the research done. The advantage of the proposed technique has been revealed in contrast to the widespread methods of differential thermal analysis (DTA). Minor differences in the results are noted when repeating «heating-cooling» cycle of the same sample many times, but the general character is retained. Characteristic peaks are observed in repetitions. The ratio between the extremum values changes insignificantly. The preliminary conclusion has been made that the developed device and the method of thermoscanning can be used in laboratory studies of fats and fatty compositions on the fact that one type of fat can replace another one.